The translation of phraseological units with animals: A gamified didactic approach - Alcaide-Martínez, Marta (Romanica Olomucensia, 2023)
Translators and interpreters agree that phraseological units (PUs) are among the most complicated components of languages to translate and interpret because of the cultural connotations and the very different images they evoke in diverse societies. Thus, the main objective of this work is to present a gamified didactic approach to the translation of animal idioms in the English-Spanish/Spanish-English linguistic combination. A three-step protocolised methodology is followed. First, the profile of the potential target sample is described. Second, 30 PUs are gathered in English and Spanish, respectively, and their equivalent translations are provided. Third, Sketch Engine serves the purpose of contextualising the chosen English expressions within sentences extracted from the English Web 2020 corpus, while CORPES XXI is employed with the Spanish phraseology. The result is a didactic proposal composed of four gamified activities (GAs) that will help train future translators and interpreters in the identification and search for equivalents of PUs containing animals. These exercises are available on two web platforms, specifically Genially and Educaplay, and enable the meaningful teaching-learning of complex phraseology in an innovative and more enjoyable way than a translated list of vocabulary. In conclusion, it is essential to lay special emphasis on these units and their translation practice so that learners and professionals are able to achieve quality equivalents. The introduction of gamification and corpora in phraseology translation opens up fascinating and promising avenues of further research.
Keywords: phraseological units (PUs); animals; corpora; translation; gamification